Editorial of the thematic dossie "Energy transition and extractive dependence: Latin America’s dilemmas in the age of critical minerals" - Santos, Leandro Bruno (Geografares, 2026)
Editorial of the thematic dossie.
Keywords: thematic dossier; energy transition; critical minerals